„Stânga” şi „dreapta” doctrinei revistei literare „Gândirea” - Iulia Belu (Revista de Istorie și Teorie Literară)
Paradoxically, in the era of globalization, it was felt the need to shift towards the national values of the interwar period. There were reprinted the eminently representative writers for the Orthodoxist traditionalism and autochthonism promoted by ˝Gândirea˝ literary review. The movement was characterized by a lack of unity, there was the right wing of ˝Gândirea˝’s doctrine, which lingered in a metaphysical belief and traditional literary values and the left wing, that put more emphasis on creativity and freedom of the movement of literary ideas.